Manual de aulas práticas de ciências no formato e-book para professores da rede pública de ensino - Theisen, Geovane Rafael (2017)
The present study presented to the Post-graduation Program in Networking Educational Technologies, in the line of research "Development of Networking Educational Technologies", aimed to investigate and discuss the theme of practical classes in Science teaching, taught by teachers of elementary level in Palmeira das Missões City/RS. For this, as a teaching product, a practical classes manual of Sciences in E-book format was developed to assist teachers in the accomplishment of practical activities. it was adopted and carried out, as methodological strategy, an applied research with predominantly qualitative approach. The data were collected through the application of a questionnaire to Science teachers and to analyze the results, it was used as a reference, the content analysis proposed by Bardin (2011), which lists three categories: initial and continued teaching training; teaching practice and the school’s infrastructure. Therefore, it was a descriptive and exploratory study. In the last phase of the research, after the development of the e-book, the product was sent to the teachers with the online evaluation and validation form. With the analysis of the results it was possible to contemplate all the objectives and respond positively to the research problem, understanding that through the practical classes provided in the e-book, it is possible to combine theory with practice and to enable the development of research and problematization in classroom, arousing curiosity, interest and building the student's knowledge.